Energy for a Sustainable World—From the Oil Age to a Sun‐Powered Future. By Dr. Nicola Armaroli and Prof. Vincenzo Balzani. Issue 8 (1st August 2014) - Wetzel, Thomas
<x xml:space="preserve">Abstract</x> Wiley‐VCH, Weinheim, 2011, 368 pp., softcover, €29.90—ISBN 978‐3‐527‐32540‐5<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>